Actinide–Pnictide (An−Pn) Bonds Spanning Non‐Metal, Metalloid, and Metal Combinations (An=U, Th; Pn=P, As, Sb, Bi). Issue 5 (29th December 2017) - Rookes, Thomas M.; Wildman, Elizabeth P.; Balázs, Gábor; Gardner, Benedict M.; Wooles, Ashley J.; Gregson, Matthew; Tuna, Floriana; Scheer, Manfred; Liddle, Stephen T.
Abstract: The synthesis and characterisation is presented of the compounds [An(Tren DMBS )Pn(SiMe3 )2 ] and [An(Tren TIPS )Pn(SiMe3 )2 ] [Tren DMBS =N(CH2 CH2 NSiMe2 Bu t )3, An=U, Pn=P, As, Sb, Bi; An=Th, Pn=P, As; Tren TIPS =N(CH2 CH2 NSiPr i 3 )3, An=U, Pn=P, As, Sb; An=Th, Pn=P, As, Sb]. The U−Sb and Th−Sb moieties are unprecedented examples of any kind of An−Sb molecular bond, and the U−Bi bond is the first two‐centre‐two‐electron (2c–2e) one. The Th−Bi combination was too unstable to isolate, underscoring the fragility of these linkages. However, the U−Bi complex is the heaviest 2c–2e pairing of two elements involving an actinide on a macroscopic scale under ambient conditions, and this is exceeded only by An−An pairings prepared under cryogenic matrix isolation conditions. Thermolysis and photolysis experiments suggest that the U−Pn bonds degrade by homolytic bond cleavage, whereas the more redox‐robust thorium compounds engage in an acid–base/dehydrocoupling route. Abstract : Heavy metals : Molecular actinide‐pnictide bonds, including the first U−Sb and Th−Sb bonds of any kind and first two‐centre‐two‐electron (2c2e) U−Bi bonds, are reported. The U−Bi bond is the heaviest 2c–2e pairing of two elements involving an actinide outside matrix isolation experiments.